Architectural models: legacy and critical perspectives - Filippo Fiandanese (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
This article investigates the theoretical legacy of the notion of model in architectural and urban discourse. This concept is characterised by a bundle of meanings, sedimented during a longstanding evolution, and by a never interrupted debate around it. The contribution will retrace the roots of the concept of model and will outlines some highpoints of the discussion, in particular in the 1970s when model became crucial in the epistemological discourse on architecture, till the recent heterogeneous resurgence. In fact, nowadays the notion of model, with its longstanding heritage, may be an effective and still up to date device to study the contemporary conception and production of space in the global stage.